Gene Expression Profiling and Response Signatures Associated With Differential Responses to Infliximab Treatment in Ulcerative Colitis - Toedter, Gary; Li, Katherine; Marano, Colleen; Ma, Keying; Sague, Sarah; Huang, Chris C; Song, Xiao-Yu; Rutgeerts, Paul; Baribaud, Frédéric (The American journal of gastroenterology, 2011)
Infliximab has been shown to induce clinical response and remission in ulcerative colitis (UC). To characterize the biological response of patients to infliximab, we analyzed the mRNA expression patterns of mucosal colonic biopsies taken from UC patients enrolled in the Active Ulcerative Colitis Trial 1 (ACT1) study. Biopsies were obtained from 48 UC patients before treatment with 5 or 10 mg/kg infliximab, and at 8 and 30 weeks after treatment (n = 113 biopsies). Global gene expression profiling was performed using Affimetrix GeneChip Human Genome U133 Plus 2.0 arrays. Expression profiling results for selected genes were confirmed using qPCR. Infliximab had a significant effect on mRNA expression in treatment responders, with both infliximab dose and duration of treatment having an effect. Genes affected are primarily involved with inflammatory response, cell-mediated immune responses, and cell-to-cell signaling. Unlike responders, non-responders do not effectively modulate T(H₁), T(H₂), and T(H₁₇) pathways. Gene expression can differentiate placebo and infliximab responders. Analysis of mRNA expression in mucosal biopsies following infliximab treatment provided insight into the response to therapy and molecular mechanisms of non-response.